Urban Sprawl and Changes in Community Lifestyle in Johor Bahru City - T. Renu, Siva Kumar; Syed Hussain, Tuan Pah Rokiah (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2019)
Previous studies are less clear discussing about the impact of urban sprawl on the lifestyle of the community. The objective of this study is to determine the differences in the lifestyle of the community in Johor Bahru City as a result of the urban sprawl. A total of 500 heads of households are involved in the survey with a 45-year-old minimum age group in the city. This study uses t-test analysis and the findings show that the overall lifestyle aspect of the community in Johor Bahru City shows a significant difference between the present and the previous as a result of the urban sprawl of all the lifestyle constructs and the overall lifestyle aspect itself.